Genetics of performance and injury: Considerations for the strength and conditioning coach - Brazier, J.; Turner, A.; Antrobus, M. (Strength and Conditioning Journal, 2024)
Genetic profiling and direct-to-consumer genetic testing have seen exponential growth in the past decade, driven by advancements in knowledge and technology making genetic information far more accessible to the population. Specifically in the sports industry, there are claims that the results from these tests can inform training and dietary practices and even identify children's athletic talents. However, in some cases, how this information is being used or promoted can be far removed from the evidence base. Because of this, anyone involved in the sports industry, such as strength and conditioning coaches, sports scientists, coaches, and parents, need to have a sound grasp of what can and cannot be taken from genetic tests. Thus, the purpose of this article is to provide a brief overview of genetics and heredity, highlight some of the key genetic findings to date regarding athletic performance and injury, and then finally provide context as to how this information can be used.